GAS-EXCHANGE OF CAPTIVE FREELY DIVING GREY SEALS (HALICHOERUS-GRYPUS) - REED, J Z; CHAMBERS, C; FEDAK, M A; BUTLER, P J (1994)
When at sea, phocids dive for long periods and spend a high percentage of their time submerged. This behaviour requires some combination of an increased oxygen storage capacity, rapid oxygen loading at the surface and reduced oxygen utilisation when submerged. To assess these adaptations, breath-by-breath ventilation was studied in four adult grey seals (two male, two female, 160-250 kg), freely diving in a large outdoor tank where surface access was restricted to one breathing hole. The dive patterns obtained were similar to those recorded from freely diving wild grey seals. Respiratory frequency during the surface periods was 40% higher than that estimated from allometric relationships (19.4+/-0.7 breaths min(-1)), and tidal volume (6.3+/-1.21) was approximately five times higher than that estimated from allometric relationships. These adaptations produce a high minute volume and enable gas exchange to occur at the surface. Mean oxygen consumption rate (V-O2 measured for a dive+surface cycle) decreased with increasing dive duration. The aerobic dive limit was estimated as 9.6min for a 150kg grey seal (using the overall average V-O2 of 5.2mO(2)min(-1)kg(-1)), which is consistent with results from freely diving wild grey seals (only 6% of dives exceeded 10 min). End-tidal oxygen values varied during a surface period, following a U-shaped curve, which suggests that there is limited oxygen uptake from the lung and/or blood oxygen stores during dives. This result was unexpected and indicates that these seals are utilising substantial physiological responses to conserve oxygen, even during shallow voluntary diving.